Prediction of body condition score in dairy cows using routine electronic data capture - Nelson, Rebecca (2025)
Body condition scoring is a widely accepted practical herd management technique used for assessing the impact of changes in energy status of adult dairy cows. Achieving optimum cow condition scores throughout lactation is necessary to maximise milk production, reproductive performance and health status and indirectly optimising overall farm profitability. However, the traditional visual body condition scoring system is subjective and can result in substantial inter and intra scorer variability. An objective and automated method of body condition scoring would be a valuable tool for the management of modern dairy herds.